Long-range conformational transition in yeast tRNAPhe, induced by the Y-base removal and detected by chloroacetaldehyde modification. - Krzyzosiak, W J (1983)
Chemical modification was used to study the conformational changes occurring in yeast tRNAPhe after the Y-base excision. The chemical probe was the adenine- and cytosine-specific reagent chloroacetaldehyde. Comparison of the modification patterns in tRNAPhe and tRNAPhe-Y shows that seven bases, adenines 35, 36 and 38 in the anticodon loop and adenines 73, 76 and cytosines 74, 75 in the 3'-terminus were modified in both tRNAs with a quantitative difference in the modification level of the anticodon loop bases. The most interesting, however, is the qualitative difference consisting in modification of cytosine-60 in the T psi C loop of tRNAPhe-Y. Some aspects of the mechanism of this long-distance conformational transition are briefly discussed.